The jet engine. - Jay, Stephen (Collier-MacMillan, 1972)
First principles -- The jet family -- The compressor -- Rotors and stators -- The combustion chamber -- Turbines -- Reheat (Afterburning) -- The exhaust system -- Noise suppresion -- Thrust reversal -- Fuel systems -- Starting and ignition -- Controls and instrumentation -- Installation and servicing -- A look at the future.